Utilizing Modified Delphi Method to select performance measures in SMEs - Nor Mahirah, Mustapha; Sorooshian, Shahryar; Noor Azlinna, Azizan (International Economic Society, 2018)
The purposes of this paper is to provides the foundations of the Delphi Method, discusses its strengths and weaknesses, gives the justifications for the selected methodology and literature review of past research, provides the guidelines for the stages followed to achieve consensus among experts that ensure validity of study, and discusses panel selection in the current study. This paper using extensive literature reviews to analyze published research on Delphi in social sciences study, explores the steps of Delphi method to achieve the consensus of experts, and its empirical applications. The Delphi method has proven as a popular judgement forecasting method in social sciences studies for identifying and prioritizing issues for managerial decision making, however it is lack of research in performance management using experts. Delphi method is the most suitable tool to be used to achieve the current objectives. In addition, the example of current study is used to demonstrate the process of variables selection. This paper helps future researchers in business management especially in SMEs to get guidelines about qualitative study, making it highly applicable in academia and commerce.